2016
DOI: 10.1515/hukin-2015-0142
|View full text |Cite
|
Sign up to set email alerts
|

Application of A Physiological Strain Index in Evaluating Responses to Exercise Stress – A Comparison Between Endurance and High Intensity Intermittent Trained Athletes

Abstract: The study evaluated differences in response to exercise stress between endurance and high-intensity intermittent trained athletes in a thermoneutral environment using a physiological strain index (PSI). Thirty-two subjects participated in a running exercise under normal (23°C, 50% RH) conditions. The group included nine endurance trained athletes (middle-distance runners - MD), twelve high-intensity intermittent trained athletes (soccer players - HIIT) and eleven students who constituted a control group. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Physiological Strain Index (PSI) based upon heart rate and body temperature measurements, allowing the instantaneous assessment of overall physiological strain on a scale of 0-10. Predictions of physiological strain may be important in determining physiological endurance and in protecting athletes against exercised induced thermal stressors (Moran et al, 1998;Pokora, Żebrowska, 2016). Physiological Strain Index calculated in our study reflects low cardiovascular strain (PSI 2.2 ±0.7).…”
Section: Discussionmentioning
confidence: 75%
“…Physiological Strain Index (PSI) based upon heart rate and body temperature measurements, allowing the instantaneous assessment of overall physiological strain on a scale of 0-10. Predictions of physiological strain may be important in determining physiological endurance and in protecting athletes against exercised induced thermal stressors (Moran et al, 1998;Pokora, Żebrowska, 2016). Physiological Strain Index calculated in our study reflects low cardiovascular strain (PSI 2.2 ±0.7).…”
Section: Discussionmentioning
confidence: 75%
“…The share of the circulatory component f HR in the contribution of the cardiovascular fraction to the PSI (circulatory strain) accounted for approx. 70–80% of the PSI volume [ 61 ] in highly trained athletes (runners and cyclists). In the current study in all subjects, the circulatory strain ( f HR) was the major component (0.76–0.77) determining the overall physiological strain during the submaximal exercise test performed before and after MPHA by elite athletes (cross-country skiers) in a thermoneutral environment.…”
Section: Discussionmentioning
confidence: 99%
“…The PSI was calculated from resting Tty and HR compared to the last exercise time point using the equation derived from Moran et al [ 34 ] with the index range from 0 to 10: 1–2 (no/little heat strain), 3–4 (low heat strain), 5–6 (moderate heat strain), 7–8 (high heat strain), and 9–10 (very high heat strain). The PSI reflects combined cardiovascular and thermoregulatory strain on a universal scale; therefore, the fractional cardiovascular and thermoregulatory systems contributions to the physiological strain were calculated according to Pokora and Żebrowska [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…7,30 Besides increased HR, cardiac output may also rise by 6-7 L/min (by 60% to 70% in relation to the increase in HR) although cardiac stroke volume has been found to remain constant or slightly increase in response to thermal stress. 35 Pilch et al 30 (reported that dry sauna-induced heat exposure led to an increase of HR from 66.6 bpm to 126 bpm (or 89.26%). This is in agreement with our results, where sample-wide HR increased by 71.74% from 78.9 bpm (HR 0 ) to 135.5 bpm (HR 20 ) and that HR was significantly larger in group BSA H than BSA L (147.0 bpm vs. 124.5 bpm, respectively; p = 0.000).…”
Section: Discussionmentioning
confidence: 99%